2017
DOI: 10.2174/1389450116666150722141906
|View full text |Cite
|
Sign up to set email alerts
|

Dicoumarol: A Drug which Hits at Least Two Very Different Targets in Vitamin K Metabolism

Abstract: Dicoumarol, a symmetrical biscoumarin can be considered as the "parent" of the widely used anticoagulant drug, warfarin. The discovery of dicoumarol's bioactive properties resulted from an investigation into a mysterious cattle disease in the 1940s. It was then developed as a pharmaceutical, but was superseded in the 1950s by warfarin. Both dicoumarol and warfarin antagonise the blood clotting process through inhibition of vitamin K epoxide reductase (VKOR). This blocks the recycling of vitamin K and prevents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 115 publications
(121 reference statements)
0
32
0
Order By: Relevance
“…23,24 However, a recent study suggests that warfarin competitively inhibits VKOR by competing with vitamin K. 25 Several studies modeling warfarin's action within model structures of VKOR have identified residues that potentially interact with warfarin. 25,26 However, no direct interaction between warfarin and the experimentally supported TY 139 A warfarinbinding motif has been observed. It is worth noting that these modeling studies used a 4-TM topology model of human VKOR, derived from the crystal structure of Syn-VKOR, which appears to have a different topological structure from human VKOR.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 However, a recent study suggests that warfarin competitively inhibits VKOR by competing with vitamin K. 25 Several studies modeling warfarin's action within model structures of VKOR have identified residues that potentially interact with warfarin. 25,26 However, no direct interaction between warfarin and the experimentally supported TY 139 A warfarinbinding motif has been observed. It is worth noting that these modeling studies used a 4-TM topology model of human VKOR, derived from the crystal structure of Syn-VKOR, which appears to have a different topological structure from human VKOR.…”
Section: Introductionmentioning
confidence: 99%
“…Warfarin is mainly metabolized by CYP-2CP microsomal liver enzymes, which is affected by a multitude of different environmental factors, diet, drug interactions, and genetics, especially CYP2 complex mutations which can alter the pharmacokinetics and pharmacodynamics of warfarin metabolism leading to toxicity and prolonged international normalized ratio (INR). [1] The prothrombin time, standardized as the INR, is used to monitor warfarin anticoagulation. Warfarin-related nephropathy (WRN) is a recently reported clinical entity, secondary to a prolonged INR.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the rate of this reductive half-reaction is strictly NADH-dependent, and thus, should be accelerated due to the HIF-mediated enhancement of aerobic glycolysis (raising cytosolic NADH levels, section 1.3.1); in a second and slower step (with a rate constant of 10 5 -10 6 M -1 •s -1 ), the oxidative half-reaction, the substrate binds and is reduced by the FADH2, thus releasing the reduced substrate and regenerating the holo-enzyme [76,79]. Dicoumarol, a potent anticoagulant and mitochondrial uncoupling agent, acts as a competitive inhibitor of NAD(P)H during the NQO1 cycle (Table A1) [87]. The high level of NQO1 expression in some cancer cells, coupled with its role in defence against ROS, has led to the suggestion that NQO1 inhibition may be a novel therapy for the disease.…”
Section: Overview Of Nqo1 Expression Regulation and Functions: On Thmentioning
confidence: 99%